Temporal variability of average and low flows in Slovak rivers: A 90-year perspective - Pavla Pekárová; Dana Halmová; Veronika Bačová Mitková; Jana Poórová; Lotta Blaškovičová; Ján Pekár; Igor Leščešen; Zbyněk Bajtek (Journal of Hydrology: Regional Studies, 2025)
Study region: Slovakia, Central Europe. Study focus: This study presents a comprehensive assessment of long-term streamflow variability in Slovakia over a 90-year period (1930/31–2019/20), based on daily discharge data from 27 near-natural catchments. The focus is on trends in average annual flows, 7-day minimum flows, seasonality of low-flow events, and spatial patterns across hydrological regions. New hydrological insights for the region: This is the first national-scale assessment of Slovak rivers using such a long continuous daily discharge dataset. The analysis reveals a marked spatial gradient in discharge trends: while mountainous regions (Region I) show stable or increasing flow conditions, lowland regions (Region III) experience significant declines — up to 27 % in average annual flow and 23 % in 7-day minimum flows. A strong positive correlation was found between specific discharge and catchment altitude. Notably, despite post-1996 increases in precipitation, runoff decreased due to rising temperatures and evapotranspiration. Minimum flows now occur up to 16 days earlier in lowlands. These results emphasize the unequal hydrological response to climate change across Slovak river basins and provide a solid foundation for future water resource planning under changing climate conditions.